2009
DOI: 10.1111/j.1360-0443.2009.02708.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of interventions to prevent alcohol‐related disease and injury in Australia

Abstract: Based on current evidence, interventions to reduce harm from alcohol are highly recommended. The potential reduction in costs of treating alcohol-related diseases and injuries mean that substantial improvements in population health can be achieved at a relatively low cost to the health sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
105
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 25 publications
7
105
1
5
Order By: Relevance
“…[4]), the underestimation of overall exposure in such surveys is not surprising. For the conclusions of Cobiac and colleagues [1] this has two consequences: first, the cost-effectiveness ratios for interventions are all underestimated: alcohol interventions such as those examined are even more cost effective compared to other interventions in the health care field. Consequently, there is an even stronger argument for alcohol policy in the current climate of rationing health care!…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[4]), the underestimation of overall exposure in such surveys is not surprising. For the conclusions of Cobiac and colleagues [1] this has two consequences: first, the cost-effectiveness ratios for interventions are all underestimated: alcohol interventions such as those examined are even more cost effective compared to other interventions in the health care field. Consequently, there is an even stronger argument for alcohol policy in the current climate of rationing health care!…”
mentioning
confidence: 99%
“…Cobiac and colleagues [1] have convincingly demonstrated that science can help the decision making of alcohol policy in the eve of a global alcohol strategy [2]. They combined sophisticated modelling in the tradition of WHO CHOICE methodology (CHOsing Interventions which are Cost Effective: http://www.who.int/choice/en/; for applications to reduce alcohol-attributable harm see [3]) with local expertise (such as derived from the Advisory Board) to compare realistic interventions in Australia for reducing alcohol-attributable health harm.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Previous studies that were part of ACE prevention reported on physical activity and alcohol interventions. 13,14 We recently reported that 'traffic-light' nutrition labelling and 'junk-food' tax offer excellent value for money as obesity prevention measures. 15 Using the same methods, the present research evaluates whether two dietary interventions to reduce overweight and obesity would be cost-effective in the Australian context.…”
Section: Introductionmentioning
confidence: 99%